Analisis Pendidik Profetik Menurut Quraish Shihab dalam Tafsir Al-Misbah Q.S Al-Jumu’ah Ayat 2 - Lathifah Irsyadiyah Husna; Dzulkifli Hadi Imawan; Melianie Putri Dewinta Sarie (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2026)
The characteristics of educators are an important aspect of educational success, because education will never be successful without competent educators in the learning process. The Qur'an is a source of human life that is always relevant throughout time. It regulates human life, including the characteristics of educators as conveyed by Allah in Q.S Al-Jumu’ah verse 2. This article aims to examine the characteristics of educators based on Q.S Al-Jumu’ah verse 2 according to Muhammad Quraish Shihab in the book Tafsir Al Misbah. The research method used is qualitative with a literature review approach. The results of the discussion indicate that the characteristics of an educator are not only to impart knowledge during the learning process, but an educator also purifies the heart, ethics, and imparts religious knowledge in the form of the Qur’an and the Sunnah. so that students can become a generation that emulates the character of the Prophet Muhammad, not only focusing on general knowledge. Q.S Al-Jumu’ah verse 2 emphasizes that educators should continue to uphold both moral character and knowledge